Le concept de “métalinguistique” dans la linguistique anglaise - Claude Boisson (Anglophonia)
This article is a detailed examination of the uses of “metalinguistic” and “metaoperation” in English linguistics, mainly in the work of Henri Adamczewski and his followers. It is shown that they suffer from serious inadequacies and confusions. Since the term “metalinguistic” must keep the canonical meaning it has always had in the logic and linguistic literatures since Tarski’s coinage of “metalanguage” in 1930, it is suggested that the “Grammaire métaopérationnelle” be renamed, as the label is misleading.